Kiss and spell - Martin, Celestine (Martin, Celestine. Elemental love, 2023)
"All Ursula Caraway wished for was to live happily ever after in her hometown of Freya Grove. The self-proclaimed Jersey Shore Witch Princess was set to begin her perfect life--until a twist of fate changed everything. Now, she's telling fortunes to the lovelorn, selling crystals at the local psychic shop, and reclaiming her missing magic. Ursula desperately wishes to shake up her life--so much so, she'll do just about anything. Including befriending a very cute, very enchanted prince. A prince in search of a kiss... Prince Xavier Alder needs to find The One, but his lack of social skills has made that a challenge--and being cursed by the Faerie Queen isn't helping either. So when Ursula, eager to believe in magic again, agrees to help Xavier find a perfect, curse--breaking kiss before Midsummer, it's the ideal opportunity for them to get what they want. So long as they don't let their mutual (and inconvenient) attraction get in the way"--